Association Study of Two Cannabinoid Receptor Genes, CNR1 and CNR2, with Methamphetamine Dependence - Okahisa, Y (Bentham Science Publishers Ltd, 2011)
Several studies have suggested that the endocannabinoid system plays significant roles in the vulnerability to psychiatric disorders including drug abuse. To examine the possible association of the CNR1 and CNR2 genes, which encode cannabinoid receptors CB1 and CB2, with methamphetamine dependence, we investigated three single nucleotide polymorphisms (SNPs) (rs806379, rs1535255, rs2023239) in intron 2 of the CNR1 gene and a nonsynonymous SNP, Q63R, in the CNR2 gene. The study samples consisted of 223 patients with methamphetamine dependence and 292 age- and sex- matched controls. There were no significant differences between the patients and controls in genotypic or allelic distribution of any SNP of the CNR1 and CNR2 genes. We also analyzed the clinical features of methamphetamine dependence. Rs806379 of the CNR1 gene showed a significant association with the phenotype of latency of psychosis after the first consumption of methamphetamine. Patients with the T allele or T-positive genotypes (T/T or A/T) may develop a rapid onset of psychosis after methamphetamine abuse. The present study suggests a possibility that genetic variants of the CNR1 gene may produce a liability to the complication of psychotic state after abuse of methamphetamine; however, our findings need to be confirmed by future replications.